Legal Theory and Legal Education - the Next Step - Charles Sampford; David Wood (Legal Education Review)
Before outlining our two approaches to incorporating legal theory into classic law subjects, some further general points are in order.First, law teachers should not expect to cover all of the material associated with a particular subject or all of the questions that could be asked about it. Just as we want students to do a fairly wide range of subjects so we want them to be confronted by a range of questions and theoretical answers to them. However, just as we do not attempt to teach every area of law in a single undergraduate law subject, so we would not attempt to pose all the theoretical questions about law nor attempt to use all the theoretical answers in a single subject. Both are tasks that can and should only be addressed by the law school as a whole rather than in individual subjects. Individual academics should ask the questions that are of interest to them and which the theory of law to which they adhere (be it a standard theory or idiosyncratic) tells them is important. This is not to say that we should all be autonomous islands in the choice of questions and theoretical answers. Some communication and cooperation between staff is necessary to ensure that students are exposed to a wide range of questions and theoretical answers to them. But this is no different from any other problem in designing the curriculum. The classic subject areas such as torts, contract, property have to be parcelled up and allocated among the staff. Not everyone can teach their favourite subjects, but the interests of a well balanced staff mean that most can teach most of those areas of law in which they are interested. As it is with the familiar division of traditional subjects, so it is with the division of theoretical elements in the curriculum.